Herbert of Bosham : a medieval polymath - Staunton, Michael, 1967- (York Medieval Press ; The Boydell Press, 2019)
Herbert of Bosham (c.1120-c.1194) is one of the most brilliant, original and versatile thinkers of the twelfth century. Herbert was Thomas Becket's closest confidant, a theologian, biblical commentator, historian, letter-writer and Hebrew scholar; he wrote a Life of St Thomas unlike any other contemporary biography, produced one of the most visually-arresting illuminated Bible books of his age, and composed a commentary on the Psalms inspired by Jewish scholarship. His uncompromising character, and the originality and complexity of his thought, meant that Herbert's works were largely ignored during his lifetime and forgotten for centuries, but more recently they have begun to receive the attention and approval that their author insisted they deserved. The chapters in this book, the first to be entirely devoted to Herbert, examine his eventful and troubled life, his remarkable corpus of works, and how they came to be neglected and rediscovered. They provide an introduction to his life, writings and legacy, direction to existing scholarship on the subject, and new insights on, interpretations of and discoveries about an idiosyncratic representative of the "twelfth-century renaissance."